2022
DOI: 10.1002/ptr.7596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea buckthorn (Hippophae rhamnoides L.) on factors related to metabolic syndrome: A systematic review and meta‐analysis of randomized controlled trial

Abstract: The purpose of this meta‐analysis is to explore whether the supplement of sea buckthorn affects the factors related to metabolic syndrome. The related RCTs from five databases were systematically searched and comprehensively random effects model was used to calculate SMD and 95% CI. The Cochrane deviation risk tool was used to evaluate the deviation risk. Fifteen studies were involved in the meta‐analysis. First, sea buckthorn supplementation reduced triglycerides [−0.722 (−1.129, −0.316); p < .001], total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Currently, there is a growing trend of systematic evaluations being conducted on medicinal and food homologous substances both domestically and internationally [ 31 33 ]. However, they are all focused on a single substance and have not been discussed and analyzed from the category of medicinal and food homologous substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a growing trend of systematic evaluations being conducted on medicinal and food homologous substances both domestically and internationally [ 31 33 ]. However, they are all focused on a single substance and have not been discussed and analyzed from the category of medicinal and food homologous substances.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this systematic evaluation was carried out. In a meta-analysis examining the effects of sea-buckthorn on factors related to metabolic syndrome [ 31 ], it was determined that sea-buckthorn can effectively improve blood lipid levels in individuals with unhealthy lipid profiles, while having no significant impact on those who are already healthy. A systematic review was conducted to investigate the effects of turmeric on liver enzymes in patients with NAFLD [ 32 ], the study found that high-dose administration of turmeric can be used as a treatment for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…fruit as folk medicine. Hippophae rhamnoides L., is widely used in medicine by the Chinese Pharmacopoeia and the World Pharmacopoeia ( Geng et al, 2022 ). Notably, among the constituents, ISO accounts for the most important and representative ingredients of H. rhamnoides L .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These modern pharmacological studies supported most traditional uses of H. rhamnoides L. fruit as folk medicine. Hippophae rhamnoides L., is widely used in medicine by the Chinese Pharmacopoeia and the World Pharmacopoeia (Geng et al, 2022). Notably, among the constituents, ISO accounts for the most important and representative ingredients of H. rhamnoides L. It is rich in nutrients, bioactive substances and various amino acids required by the human body, especially high in vitamins.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The fatty acids, organic acids, amino acids, vitamins and minerals are also present in H. rhamnoides L. preparations (Sławińska et al, 2023b;Wang et al, 2022;Żuchowski, 2023). Moreover, it is a valuable plant with many biological and pharmacological properties described over the last 2 years by many authors: antioxidant (Nowak et al, 2022;, antimicrobial (Nowak et al, 2022;Wang et al, 2022), treating metabolic syndrome (Geng et al, 2022;Chen et al, 2023), anticancer (Visan et al, 2023), anti-osteoporosis (Park et al, 2022), antihyperlipidemic (Kopčeková et al, 2023), anti-inflammatory (Laskowska et al, 2022;Zhou et al, 2023), antifatigue effect (An et al, 2023), dermatological (Skowrońska and Bazylko, 2023), neuroprotective (Lan et al, 2023), hepatoprotective (Ma et al, 2023).…”
Section: Sea Buckthorn Plant As a Functional Food Ingredient With Ant...mentioning
confidence: 99%